PENGARUH KEPUASAN KERJA DAN MOTIVASI TERHADAP TURNOVER INTENTIONS DENGAN KOMITMEN SEBAGAI VARIABEL MEDIASI (Survey Karyawan Pada Sektor Retail “Alfa Mart”) - Soekiyono Soekiyono (Universitas Muhammadiyah Metro Lampung, 2017)
The aims of this research is to know the relation of employee satisfaction to employee's motivation, employee satisfaction influence to employee commitment, employee satisfaction influence to turnover intentions, influence of motivation to commitment, motivation influence to turnover intentions, and influence commitment to turnover intentions. The research was conducted on employees of retail company Alfa Mart. The sample used in this study as many as 180 respondents. The analytical method used is structural equation modeling analysis.Based on the results of data analysis, it can be concluded that job satisfaction is positively related to work motivation, as well as the higher the work motivation, the easier it will be for an employee to feel satisfied in working. Job satisfaction positively affects commitment. Job satisfaction negatively affects turnover intention. Motivation positively affects commitment. Motivation negatively affects turnover intention. Commitment negatively affects turnover intention.The results of this research produced suggestions to the management of Retail Alfa Mart company that management increases employee commitment by improving motivation and employee satisfaction. Turnover intention needs to be identified more quickly so that employees do not intend to quit the job. This needs to be improved by increasing job satisfaction, work motivation and employee commitment to the company. For further research it is necessary to examine the length of service and serve as a moderating variable to identify turnover intention. It is necessary to know the motivation, satisfaction and commitment and influence on turnover intention with the working period as a variable that weakens or strengthens the influence among these variables. Keywords: Employee satisfaction, employee motivation, employee commitment, turnover intentions